1996
DOI: 10.1557/jmr.1996.0330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cubic diamond in the graphite-magnesium carbonate and graphite-K2Mg(CO3)2 systems at high pressure of 9–10 GPa region

Abstract: Cubic diamond was synthesized with two systems, (1) graphite with pure magnesium carbonate (magnesite) and (2) graphite with mixed potassium and magnesium carbonate at pressures and temperatures above 9.5 GPa, 1600 ± C and 9 GPa, 1650 ± C, respectively. At these conditions (1) the pure magnesite is solid, whereas (2) the mixed carbonate exists as a melt. In this pressure range, graphite seems to be partially transformed into hexagonal diamond. Measured carbon isotope d13 C values for all the materials suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…1). This phase was previously observed as a quench product in some high-pressure experiments on diamond and wadsleyite growth (Shatskiy et al, 2009;Taniguchi et al, 1996) and in experiments on carbonated peridotite (Brey et al, 2011), but was not characterized. The new K-Ca phase is stable over the entire studied pressure range but becomes dominant in the Na carbonatite subsolidus assemblage at 21 GPa only; its structure is yet to be determined.…”
Section: Resultsmentioning
confidence: 92%
“…1). This phase was previously observed as a quench product in some high-pressure experiments on diamond and wadsleyite growth (Shatskiy et al, 2009;Taniguchi et al, 1996) and in experiments on carbonated peridotite (Brey et al, 2011), but was not characterized. The new K-Ca phase is stable over the entire studied pressure range but becomes dominant in the Na carbonatite subsolidus assemblage at 21 GPa only; its structure is yet to be determined.…”
Section: Resultsmentioning
confidence: 92%
“…The absence of any evidence for an accumulation of this kind of melts at the base of the lithosphere, where temperatures would be low enough for complete crystallization of the carbonatite melts, suggests that a redox reaction with the reduced mantle (Frost and McCammon 2008;Rohrbach et al 2009) immobilizes these carbonatites. In fact, diamond crystallization has been shown to be favored by the catalytic behaviour of K 2 CO 3 -rich melt and fluid (Taniguchi et al 1996;Palyanov et al 2007;Klein-BenDavid et al 2007).…”
Section: Evidence For Subducted Carbonates and K-rich Metasomatism Inmentioning
confidence: 99%
“…The fi rst group has been the most extensively explored, with solvents or catalysts (other than transition metal melts) such as kimberlitic melts (Arima et al 1993), solid or liquid carbonate (Akaishi et al 1990;Taniguchi et al 1996;Pal'yanov et al 1999aPal'yanov et al , 1999bPal'yanov et al , 2002aSato et al 1999;Sokol et al 2000Sokol et al , 2001aSpivak and Litvin 2004;Tomlinson et al 2004), sulfi de melts (Pal'yanov et al 2001;Sato and Katsura 2001), and both oxidized (CO 2 -H 2 O) and reduced (CH 4 -H 2 O) fl uids (Yamaoka et al 1992(Yamaoka et al , 2002a(Yamaoka et al , 2002bKumar et al 2000Kumar et al , 2001Sun et al 2000;Akaishi et al , 2001Sokol et al 2001b;Okada et al 2002;Dobrzhinetskaya et al 2004). To the authors' knowledge, no study has reported oxidation of a reduced, carbon-bearing (e.g., CH 4 -rich) fl uid to produce diamond in the absence of graphite or another source of carbon.…”
Section: Introductionmentioning
confidence: 99%